Oxidative stress and inflammatory mediators contribute to endothelial dysfunction in high-fat diet-induced obesity in mice - Kobayasi, Renata; Akamine, Eliana H.; Davel, Ana P.; Rodrigues, Maria Aparecida Marchesan [UNESP]; Carvalho, Carla R. O.; Rossoni, Luciana V. (Lippincott Williams & Wilkins, 2010)
Objective We investigated the effects of high-fat diet-induced obesity on vascular proinflammatory factors and oxidative stress on endothelium-dependent relaxation of the aorta.Methods Female Swiss mice were submitted to a high-fat diet for 16 weeks. At the end of the experimental period, we evaluated blood pressure, relaxation in response to acetylcholine in aortic rings in the absence and the presence of the superoxide anion scavenger, superoxide dismutase (SOD, 150 U/ml), and the nuclear factor (NF)-kappa B inhibitor, sodium salicylate (5 mmol/l). Aortic protein expression of endothelial nitric oxide synthase, Cu/Zn-SOD, NF-kappa B, I kappa B-alpha, and proinflammatory cytokines were also evaluated.Results Obese mice presented higher systolic and diastolic blood pressure than control mice (P<0.05). The relaxation of aortas to acetylcholine, but not to sodium nitroprusside, was significantly decreased in obese mice and was corrected by both SOD and sodium salicylate (P<0.05). The protein expression of endothelial nitric oxide synthase and Cu/Zn-SOD was significantly decreased in aorta from obese mice (P<0.05). Total p65 NF-kappa B subunit protein expression was not affected by obesity, but the protein expression of NF-kappa B inhibitor I kappa B-alpha was lower in aorta from obese mice (P<0.05). There were no significant differences in the interleukin (IL)-1 beta and IL-6 protein expression between groups. In contrast, the expression of TNF-alpha was significantly increased in aortas from obese mice.Conclusion Our resultssuggest that the reducedantioxidant defense and the local NF-kappa B pathway play an important role in the impairment of endothelium-dependent relaxation in aorta from obese mice. J Hypertens 28: 2111-2119 (C) 2010 Wolters Kluwer Health vertical bar Lippincott Williams & Wilkins.
Keywords: endothelial dysfunction; NF-kappa B; obesity; proinflammatory cytokines